Development of a Local Area Network-Based Filing System for Outgoing and Incoming Letters in The General Service of The Samboja Sub-District - Afrah Dewi Fortuna; Asep Nurhuda; Yulianto (TEPIAN, 2023)
archives are defined as a place to store important records or documents. Archives are generally written documents in any environment that have historical value or an obligation to keep them. Archiving and recording of letters are still done manually which makes finding documents difficult and time-consuming. Therefore, it is necessary to design an application to assist the head of the study program in finding incoming and outgoing mail reports. The Samboja sub-district office has difficulty managing the filing of incoming and outgoing letters. Work at the sub-district office is work that involves a lot of data or information that must be recorded or processed regularly so that everything related to the data or information has a certain use or value so that the archive is needed to facilitate the search process. By storing this data or information, a record is obtained which is called an archive. It can be said that the current filing system is less efficient and effective because incoming mail and outgoing mail data often do not match the incoming mail and outgoing mail data, and all processes are still carried out manually